Effectiveness of Graduality, Escalation and Argumentation in Quranic Politeness Discourse “Surat Ghafir a Model” A Pragmatic Study (Journal of the College of Education for Women, 2019)
Theauthor addressed politeness discourse in “Surat Ghafir”. Quran texts include many rhetorical utterances which are considered pragmatic mechanismsconcerned with finding polite discourse. examining these texts allow to determine the effectiveness degree in the discourse, and to find the effect level that leads to interaction between the speaker and the listener. Graduation is considered an effect and a mechanism of discourse escalation.The author reached a common definition of the graduation effectiveness term, due to its importance in finding polite discourse that is constructed by lingual manifestations some of which are escalation and graduation. Escalation is a mechanism to show the level of discourse graduation, it is a means of effectiveness that establish effective interaction between speakers by lexical and linguistic formulas and styles to show escalation amount in “Surat Ghafir”.Argumentation is examined being a graduation effectiveness mechanism that gives aneffective persuasive power, because it is subjected to inference and reasoning.Fallacy, lingual, deceptive, deductive and comparative argumentationtypes are discussed, examples from “Surat Ghafir” are provided for each type.